Dampak Insektisida Deltametrin Konsentrasi Subletal pada Perilaku dan Biologi Parasitoid - Meilin, Araz; Praptana, R. Heru (Iptek Tanaman Pangan, 2014)
Parasitoids are natural enemies of insect pests that can be used for biological pest control. Effective performance of parasitoid on the insect pest can be disrupted by the use of insecticides. This paper discussed the effect of insecticides on parasitoids, as well as the effect of deltamethrin insecticide on the behavior and biology of parasitoids. The effect of insecticides on parasitoids generally was studied by using sublethal dosage. Review of literatures indicated that deltamethrin insecticide disturbed parasitoids which affected the nervous system, and ultimately changed the behavior and biology of parasitoids. Inappropriate use of insecticide in the field reduced the ability of parasitoids in controlling insect pests.